1999
DOI: 10.1046/j.1365-2958.1999.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel sensing mechanisms and targets for the cAMP–protein kinase A pathway in the yeast Saccharomyces cerevisiae

Abstract: The cAMP–protein kinase A (PKA) pathway in the yeast Saccharomyces cerevisiae plays a major role in the control of metabolism, stress resistance and proliferation, in particular in connection with the available nutrient conditions. Extensive information has been obtained on the core section of the pathway, i.e. Cdc25, Ras, adenylate cyclase, PKA, and on components interacting directly with this core section, such as the Ira proteins, Cap/Srv2 and the two cAMP phosphodiesterases. Recent work has now started to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
572
1
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(602 citation statements)
references
References 110 publications
(168 reference statements)
20
572
1
9
Order By: Relevance
“…All phenotypes displayed by Stp1-expressing strains are consistent with a down-regulation of the Ras branch of the cAMP-pathway that plays a key role in stress resistance and nutrient sensing (reviewed in Thevelein & deWinde, 1999), although we cannot exclude that other, previously identified S. cerevisiae substrates for Stp1, including enzymes involved in carbon metabolism (Modesti et al, 2001) and the immunophillin Fpr3 Marchetta et al, 2004), may contribute to one or more of the phenotypes here reported. The evidence for a cross-talk between a tyrosine phosphorylation/dephosphorylation pathway(s) and the Ras/PKA pathway is many fold, since Stp1-expressing cells share a number of phenotypes with mutants with attenuated Ras/PKA pathway.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…All phenotypes displayed by Stp1-expressing strains are consistent with a down-regulation of the Ras branch of the cAMP-pathway that plays a key role in stress resistance and nutrient sensing (reviewed in Thevelein & deWinde, 1999), although we cannot exclude that other, previously identified S. cerevisiae substrates for Stp1, including enzymes involved in carbon metabolism (Modesti et al, 2001) and the immunophillin Fpr3 Marchetta et al, 2004), may contribute to one or more of the phenotypes here reported. The evidence for a cross-talk between a tyrosine phosphorylation/dephosphorylation pathway(s) and the Ras/PKA pathway is many fold, since Stp1-expressing cells share a number of phenotypes with mutants with attenuated Ras/PKA pathway.…”
Section: Discussionsupporting
confidence: 76%
“…cAMP-activated PKA phosphorylates a number of proteins involved in metabolism, cell cycle progression, accumulation of glycogen and trehalose and heat-shock resistance. Reduced activity of this pathway leads to growth arrest at the beginning of G1 phase (the same stage at which the cells arrest following nutrient deprivation), causes enhanced levels of glycogen and trehalose and constitutive expression of heat-shock genes (reviewed in Rolland, Winderickx, & Thevelein, 2002;Thevelein & deWinde, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, glucose reduction (2-0.5%) increases protection against oxidative stress, whereas complete starvation by switching the population of cells to water, promotes protection to oxidative insults and heat shock and a major life span increase (Longo et al, 1997;Wei et al, 2008). Although the precise molecular mechanisms of increased protection by fasting have yet to be described in detail, in yeast they involve the reduced activity of the Ras/cAMP/PKA and the Tor/S6K nutrient signaling pathways and the activation of transcription factors downregulated by these pathways (Thevelein and de Winde, 1999;Wei et al, 2008). In fact, deletion of transcription factors Msn2/Msn4 and Gis1 reverses the protection caused by glucose restriction or starvation conditions, suggesting an important role for genes involved in metabolism, cellular protection and repair regulated by these factors in starvation-dependent stress resistance (Longo et al, 1997;Wei et al, 2008).…”
Section: Starvation and Stress Resistancementioning
confidence: 99%
“…The S. cerevisiae Msn2p and Msn4p zinc finger proteins are responsive to the general stress response (Martínez-Pastor et al, 1996), and are repressed by the cAMP-dependent protein kinase A (PKA), which is regulated by the Ras/cAMP signalling pathway (Boy-Marcotte et al, 1998;Marchler et al, 1993). cAMP activates PKA by binding to the Bcy1p regulatory subunit, and dissociation of the Tpk1/2/3p catalytic subunits (Thevelein and de Winde, 1999). The S. cerevisiae heat shock factor (Hsf1p) activates the transcription of genes containing heat shock elements in their promoter, like those encoding heat shock proteins (Hsp).…”
Section: Introductionmentioning
confidence: 99%